Cannabidiol prescribing in the United States: An analysis of real-world data - Binx Yezhe Lin; Chloe Lessard; Yifan Li; Lisa Gong; Ruth Ling; Pallawi Jyotsana; Jacob Steinle; Jacob T. Borodovsky; Fábio A. Nascimento; Kevin Y. Xu (Drug and Alcohol Dependence Reports)
Background: Off-label prescribing of Epidiolex® (pharmaceutical cannabidiol) comes with both potential benefits and risks for patients. The aims of this study were to: (1) identify the percentage of people prescribed Epidiolex® who do not have diagnostic indications for Epidiolex® (Lennox Gastaut Syndrome [LGS], Dravet Syndrome [DS], and Tuberous Sclerosis Complex [TSC]) and (2) examine potential co-prescribing of medications that may interact with Epidiolex®. Method: Using TriNetX analytics, a web-based database of de-identified electronic health records spanning >110 million people in the United States, we analyzed 4214 people receiving Epidiolex® in 2022. We computed the number of people prescribed Epidiolex® who did not have diagnoses for LGS, DS, or TSC. We evaluated the prevalence of co-occurring prescriptions that are known to interact with cannabidiol following each individual’s first Epidiolex® prescription. Results: Among individuals receiving Epidiolex®, 40 % did not have FDA-approved diagnostic indications (LGS/DS/TSC) in the medical record. In the overall sample, co-occurring psychotropic prescribing was prevalent, including medications with known interactions with cannabidiol (Clobazam=47.2 %; Diazepam=47.4 %; Clonazepam=40.7 %). Among individuals without LGS/DS/TSC who received Epidiolex®, the most common diagnoses received following the index prescription were unspecified epileptic syndromes (53.8 %), sleep disorders (25.7 %), anxiety disorders (25.9 %), mood disorders (18.6 %) and autism spectrum disorders (10.8 %). Conclusion: Off-label prescribing and co-prescription of medications with known interactions with cannabidiol is prevalent. Further research is needed to elucidate longitudinal outcomes associated with off-label Epidiolex® prescribing.